Calculation of Un-Fired Carbon Content of Circulating Fluidized Bed Combustion Ash - Chen, C.; Li, Q.; Tao, C.L.; Zhai, J.P.; Tao, D.J. (Asian Journal of Chemistry, 2012)
The circulating fluidized bed combustion ash was studied to determine its un-fired carbon content. The differential scanning calorimetry and the thermal reaction process of circulating fluidized bed combustion ash includes 3 main stages: (a) escape of moisture and volatiles; (b) carbon oxidation and mineral decomposition; (c) continuing reaction. The thermal reaction process is greatly affected by the minerals in original ash. The typical loss-on-ignition method can not used for estimating the carbon content in circulating fluidized bed combustion ash because of the interference of mineral transformation in heat treatment. A method comparing the TG, DTG, DSC curve under nitrogen and oxygen atmosphere to determine carbon content of circulating fluidized bed combustion ash is improved.